2020
DOI: 10.1136/jitc-2020-001314
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram for predicting mortality in patients with COVID-19 and solid tumors: a multicenter retrospective cohort study

Abstract: BackgroundIndividualized prediction of mortality risk can inform the treatment strategy for patients with COVID-19 and solid tumors and potentially improve patient outcomes. We aimed to develop a nomogram for predicting in-hospital mortality of patients with COVID-19 with solid tumors.MethodsWe enrolled patients with COVID-19 with solid tumors admitted to 32 hospitals in China between December 17, 2020, and March 18, 2020. A multivariate logistic regression model was constructed via stepwise regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“… 3 Nevertheless, several underlying diseases, such as cancer, hypertension, and cardiovascular diseases, act as risk factors for severe COVID-19 or COVID-19-related mortality. 2 12 32 In COVID-19 patients with cancer, systemic immunosuppression associated with the cancer itself or anticancer therapy might affect the vulnerability to severe COVID-19 or COVID-19-related mortality, which is consistent with our findings. Diabetes, known to be a hazardous comorbidity in fatal COVID-19 cases, was also associated with COVID-19-related mortality in the present study.…”
Section: Discussionsupporting
confidence: 91%
“… 3 Nevertheless, several underlying diseases, such as cancer, hypertension, and cardiovascular diseases, act as risk factors for severe COVID-19 or COVID-19-related mortality. 2 12 32 In COVID-19 patients with cancer, systemic immunosuppression associated with the cancer itself or anticancer therapy might affect the vulnerability to severe COVID-19 or COVID-19-related mortality, which is consistent with our findings. Diabetes, known to be a hazardous comorbidity in fatal COVID-19 cases, was also associated with COVID-19-related mortality in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Lymphocyte infiltration in the tumor is also associated with a better response to immunotherapy and prognosis in solid tumor patients ( 29 ). LDH and dNLR are independent risk factors for mortality among patients, and are correlated with poor outcomes in several solid cancer types according to the current evidence ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 86%
“…Solid tumor mortality of 12% and hematological malignancy of 14% were found in a study done by the COVID-19 and Cancer Consortium (CCC19). One study from the Memorial Sloan Kettering Cancer Center (MSKCC) reported the CFR as 12% [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%